Pengaruh Murottal Al-Qur’an tehadap Dosis Obat Anestesi Umum dan Waktu Pulih Sadar pada Pasien Operasi di Rumah Sakit Ibnu Sina Makassar - Abdullah, Rezky Putri Indarwati; Amkar, Musvirah Safitri; Pranomo, Sigit Dwi; Sommeng, Faisal; K, Irna Diyana Kartika (Universitas Batanghari Jambi, 2024)
General anesthesia is used to facilitate surgery by providing hypnotic effects, analgesic effects, and muscle relaxation effects. To provide an adequate hypnotic, analgesia and relaxation effect, an adequate dose is needed. The time to recover consciousness after anesthesia is determined by the volume of fluid in the body, drug metabolism, half-life of the drug, age, and pre-anesthesia status. Murottal Al-Qur'an is a non-pharmacological therapy that can reduce stress hormones, increase feelings of relaxation, divert feelings of fear, improve the body's chemical balance thereby reducing hemodynamics. The aim of this study was to determine the effect of murottal Al-Qur'an on the dose of general anesthesia and the time to recover consciously in surgical patients at Ibnu Sina Hospital, Makassar. The research method is cross sectional with a quantitative approach. Each group measured the level of sedation using a Ramsay score of 3 or 4, then calculated the time to recover consciousness. The control group was given 1 mg Â± 2 mg midazolam until they reached a Ramsay score of 3 or 4, the treatment group was given Al-Qur'an murottal and 1 mg Â± 2 mg midazolam until they reached a Ramsay score of 3 or 4. So the time to recover consciousness and the onset of sedation was fast. These results show the influence of murottal Al-Qur'an on the dose of general anesthesia and the time to recover consciousness in surgical patients at Ibnu Sina Hospital Makassar.